The long-distance leader : rules for remarkable remote leadership - Eikenberry, Kevin, 1962-; Turmel, Wayne (BK business book., 2018)
Filled with exercises that ensure projects stay on track, keep productivity and morale high, and build lasting relationships, this book is the go-to guide for leading effectively, no matter where people work. --